Health Systems Science: A Third Pillar of Medical Education - Rano Mal Piryani; Suneel Piryani (Journal of Liaquat University of Medical & Health Sciences, 2025)
After the Flexner report more than a century ago (published in 1910) and subsequent curricular reforms in medical education, medical education and its curriculum have continuously evolved concerning advancement in medical sciences and technology globally, especially in developed countries1. With the guidance of Abraham Flexner, William Osler, and other medical educationists, a curriculum was developed in the early twentieth century, focusing on students’ learning in the preclinical and clinical years, which is now commonly referred to as a traditional curriculum. This curriculum is based on two pillars, namely fundamental or foundational science and clinical science.